ترشيد استعمالات المياه للأغراض المختلفة وخاصة الزراعية في سورية - خدام, منذر; صقر, محمد; عطية, قصي (Latakia University Journal - Economic and Legal Sciences Series, 2019)
تعاني الموارد المائية في سورية من الندرة بالمقارنة مع الطلب المتزايد عليها من جرّاء زيادة السكان وتطور حياتهم الثقافية والاجتماعية والاقتصادية, مما تطلب من السلطات المعنية البحث عن الإمكانيات التي لا تزال متاحة لتنمية الموارد المائية سواء عن طريق بناء السدود أو استكشاف الأحواض الجوفية ، وكذلك تنمية مصادر المياه غير التقليدية من صرف صحي وزراعي ، والبحث الجاد عن ترشيد استعمالات المياه في الأغراض المختلفة وخصوصاً الزراعية. في هذا المجال وكما بينت الدراسة ثمة إمكانيات كبيرة غير مستفاد منها خصوصاً في مجال ترشيد استعمالات المياه أي ما يسمى بالتنمية السلبية ، فمن خلال تعميم طرق الري الحديثة أي طريقة الري بالرش أو بالتنقيط على نحو (50) بالمائة من المساحات المروية يمكن أن يوفر ذلك نحو (35) بالمائة من إجمالي المياه المستخدمة في الري، بالإضافة إلى زيادة كفاءتها بنسبة لا تقل عن (25- 30) بالمائة بحسب المحصول المروي, وكذلك فإن إعادة تجديد وصيانة شبكات الري وخصوصاً الانتقال إلى الشبكات تحت الأرضية بدلاً من الشبكات السطحية، وكذلك تجديد وتحديث شبكات التزويد بالمياه إلى المنازل يمكن أن يوفر مالا يقل عن مليار م3 من المياه في السنة. في هذا المجال بينت الدراسة ضرورة استخدام اللوائح الاقتصادية والقانونية مثل الأسعار والغرامات والعقوبات الجزائية إذا اقتضى الأمر, لما لها من أثر إيجابي على ترشيد استعمالات المياه والحفاظ عليها من الهدر وحمايتها من مخاطر التلوث وتدني نوعيتها. وفي نهاية البحث تم استعراض أهم النتائج والمقترحات التي تم التوصل إليها. Water resources in Syria are getting rare due to increasing demand as a result of population increase and improvement in people's cultural, social, and economic conditions. The authorities concerned are, therefore, required to search for possibilities to develop existing water resources through either constructing new dams, or exploring subterranean basins. Utilization of sewage water discharges and development of unconventional water resources are also ways of economization of water resources, especially for agricultural purposes. The study shows that there are possibilities not exploited yet, particularly in water economization called negative development. For example, generalizing modern irrigation systems, such as irrigation by sprinkling or dripping on 50% of irrigated areas may save 23% of the total amount of water used in irrigation and increase efficiency rate up to 25-30%, depending on the crop irrigated. Moreover, maintenance and renovation of existing irrigation networks, especially replacing surface networks by underground ones, as well as modernizing networks supplying freshwater to houses may save no less than a billion square meter of water a year. In this respect, the study emphasizes the need for the application of economic and legal regulations, such as prices, fines, and penalties, if need be, to lead people to economize in water use, lessen water wastage, and prevent pollution and deterioration of water quality. In the end, the study provides its most important conclusions, results, and suggestions.